FENOMENA DAKWAH DIGITAL DI KALANGAN SANTRI: SUATU ANALISIS ERA SWIPE DAN SCROLL - Fitriah Fitriah; Syafiin Mansur, Umu Hani, Rizka Najiyah, Muthia Rizky Nabila (ADISAM PUBLISHER, 2025)
The development of digital technology has changed the paradigm of da'wah in Indonesia, including among students. The phenomenon of digital da'wah is characterized by the use of social media platforms such as YouTube, TikTok, Instagram, and podcasts, along with the culture of